Efektivitas QR Code sebagai Media Akses Konten Digital pada Buku Mata Pelajaran Biologi untuk Meningkatkan Pemahaman Siswa SMA Kelas XI : [The Effectiveness of QR Code as a Media for Accessing Digital Content in Biology Textbooks to Improve the Understanding of Grade XI High School Students] - Rudy Pratama; Sendy Wulandhary; Padre Pio (Jurnal Teropong Pendidikan, 2025)
This research aims to explore the effect of QR codes as a digital content access tool in high school biology textbooks on the comprehension of 11th-grade students and to examine potential gender-based differences. Adopting a quasi-experimental design with a post-test-only non-equivalent group model, the study compared an experimental group (students using QR codes) and a control group (students not using QR codes). Data was collected through a standardized post-test given to thirty students in each group, following validity and reliability tests conducted on a different set of thirty students. The data analysis included normality tests, homogeneity tests, and hypothesis testing to analyze the quantitative data. The results revealed a significant improvement in the comprehension of students using QR codes, as their post-test scores were considerably higher than those in the control group. Statistical analysis of averages confirmed the effectiveness of QR codes in offering additional accessible and engaging content, such as videos, images, and articles related to the subject. Interestingly, no significant difference in comprehension was found between male and female students, suggesting that the advantages of QR codes are evenly distributed across genders. This study highlights the value of QR codes as a digital content access medium for enhancing learning outcomes in secondary school biology education, fostering an interactive and comprehensive learning experience.